SYSTEMATIZING THE CONTENT OF PRIMARY EDUCATION ON THE BASIS OF THE AXIOLOGICAL PARADIGM: THE “VALUE-CONTENT-ACTIVITY-REFLECTION” INTEGRATIVE MODEL - Shabbazova Dilfuza Ruzikulovna (International Journal of Literature and Language Studies, 2026)
The transformation of educational goals under the conditions of global informatization has shifted the focus of primary schooling from the transmission of knowledge toward the formation of value-oriented competences. This study addresses the insufficiently developed problem of reconstructing primary education content on an axiological basis, proposing and empirically validating an integrative pedagogical model built on the sequence “value–content–activity–reflection”. The model integrates axiological, learner-centred and competence-based approaches and organizes content around five interrelated components: value, cognitive, activity, reflective and integrative. A pedagogical experiment was conducted in primary classes using a triangulated methodology that combined questionnaires, observation cards, structured interviews, problem-situation analysis, content analysis and statistical processing, with experimental and control groups. Following the intervention, the experimental group demonstrated marked gains: awareness of the essence of values rose from 45% to 73%, practical application of values from 38% to 63%, value-based decision-making from 40% to 67%, and activity and respect in collaborative work from 52% to 74%. The findings confirm that systematizing primary education content through the proposed model strengthens not only academic outcomes but also the moral, social and reflective development of learners. The model is recommended for wider implementation in the design of curricula, textbooks and teacher-training programmes.